Copper clad laminate and method for manufacturing copper clad laminate

By dry plating on the thermoplastic resin base film, the problem of wrinkling of the thermoplastic resin film at high temperature is solved, and the high-frequency performance and productivity of the flexible printed circuit board are improved.

CN112601370BActive Publication Date: 2025-01-14SUMITOMO METAL MINING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010169581.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-02
Filing Date
2020-03-12
Publication Date
2025-01-14
Estimated Expiration
2040-03-12

AI Technical Summary

Technical Problem

Thermoplastic resin film is prone to wrinkles at high temperatures, resulting in a decrease in productivity of flexible printed circuit boards and it is difficult to effectively suppress the generation of wrinkles.

Method used

The base metal layer is formed on the surface of the thermoplastic resin base film by dry plating, with an average film thickness of 0.3 to 1.9 nm. The base metal layer composed of alloy materials such as nickel, chromium, vanadium, titanium, molybdenum, etc. is used, and the surface is on it. The film-forming copper layer, the base film can be composed of liquid crystal polymer, polyether ether ketone and other materials, and the adhesion is improved through dehydration and surface modification treatment.

Benefits of technology

Effectively maintain the adhesion between the resin film and the conductor layer, suppress the generation of wrinkles, improve the heat resistance and high-frequency signal processing capabilities of the flexible printed circuit board, and ensure the peel strength and transmission performance of the line.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112601370B_ABST
    Figure CN112601370B_ABST
Patent Text Reader

Abstract

The present invention provides a copper-clad laminated board which maintains the adhesion between a resin film and a conductor layer and suppresses the generation of wrinkles. The present invention is a copper-clad laminated board (1), which comprises: a base film (10) composed of a thermoplastic resin, a base metal layer (21) formed on the surface of the base film (10) by a dry plating method, and a copper layer (22) formed on the surface of the base metal layer (21). The average film thickness of the base metal layer (21) is 0.3 to 1.9 nm. Since the average film thickness of the base metal layer (21) is greater than 0.3 nm, the adhesion between the base film (10) and the conductor layer (20) can be maintained. Since the average film thickness of the base metal layer (21) is less than 1.9 nm, the temperature rise of the base metal layer (21) during film formation can be suppressed, and the generation of wrinkles can be suppressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper clad laminate and a method for producing the same. More specifically, the present invention relates to a copper clad laminate used for producing a flexible printed circuit board (FPC) and a method for producing the same. Background Art

[0002] Flexible printed circuit boards having circuit patterns formed on the surface of a resin film are used in electronic devices such as liquid crystal panels, notebook computers, digital cameras, and mobile phones. Flexible printed circuit boards are manufactured from copper-clad laminates in which copper foil is laminated on a resin film.

[0003] The amount of information processed by electronic devices is increasing year by year. Therefore, there is a need for flexible printed circuit boards installed in electronic devices to process high-frequency signals. The insulating resins used in the resin film of flexible printed circuit boards include thermosetting resins and thermoplastic resins. Among them, thermoplastic resins can be given properties of low dielectric constant and low dielectric loss depending on the type. The film composed of such thermoplastic resins is suitable for flexible printed circuit boards for high frequencies.

[0004] Patent Document 1 discloses a plated laminated body, which is formed by laminating a base layer and a copper layer on a liquid crystal polymer film as a thermoplastic resin film. The base layer is a layer composed of nickel, chromium, an alloy containing nickel, or an alloy containing chromium, which is formed by sputtering to a thickness of 2 to 30 nm. By providing the base layer, the adhesion between the resin film and the conductor layer can be improved.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-233891. Summary of the invention

[0008] However, since a thermoplastic resin film does not have the same heat resistance as a thermosetting resin film, the film temperature may increase during the formation of the base layer, causing the film to change and wrinkle, thereby reducing productivity.

[0009] In view of the above circumstances, an object of the present invention is to provide a copper-clad laminated board which maintains the adhesion between a resin film and a conductor layer and suppresses the generation of wrinkles, and a method for producing the copper-clad laminated board.

[0010] The copper-clad laminate of the first invention is characterized in that it comprises: a base film composed of a thermoplastic resin, a base metal layer formed on the surface of the above-mentioned base film by a dry plating method, and a copper layer formed on the surface of the above-mentioned base metal layer, and the average film thickness of the above-mentioned base metal layer is 0.3 to 1.9 nm.

[0011] The copper-clad laminate according to the second invention is characterized in that, in the first invention, the base metal layer has an average film thickness of 0.3 to 1.5 nm.

[0012] The copper-clad laminate of the third invention is characterized in that, in the first or second invention, the base metal layer is composed of an alloy containing at least two elements selected from the group consisting of nickel, chromium, vanadium, titanium, molybdenum and copper.

[0013] The copper-clad laminate of the fourth invention is characterized in that, in any one of the first to third inventions, the entire base film or the surface layer is a film composed of liquid crystal polymer, polyetheretherketone, polyethylene naphthalate, fluororesin, thermoplastic polyimide or cycloolefin polymer.

[0014] The manufacturing method of the copper-clad laminate of the fifth invention is characterized in that it includes: a process of forming a base metal layer on the surface of a base film composed of a thermoplastic resin by a dry plating method; and a process of forming a copper layer on the surface of the aforementioned base metal layer, and the average film thickness of the aforementioned base metal layer is 0.3 to 1.9 nm.

[0015] The method for producing a copper-clad laminate according to a sixth invention is characterized in that, in the fifth invention, the base metal layer has an average film thickness of 0.3 to 1.5 nm.

[0016] The method for manufacturing a copper-clad laminate according to the seventh invention is characterized in that, in the fifth or sixth invention, the base metal layer is composed of an alloy containing at least two elements selected from the group consisting of nickel, chromium, vanadium, titanium, molybdenum and copper.

[0017] The manufacturing method of the copper-clad laminate of the 8th invention is characterized in that, in any one of the 5th to 7th inventions, the entirety or the surface layer of the aforementioned base film is a film composed of a liquid crystal polymer, polyetheretherketone, polyethylene naphthalate, a fluororesin, a thermoplastic polyimide or a cycloolefin polymer.

[0018] According to the present invention, since the average film thickness of the base metal layer is 0.3 nm or more, the adhesion between the base film and the conductor layer can be maintained. In addition, since the average film thickness of the base metal layer is 1.9 nm or less, the temperature rise of the base metal layer during film formation can be suppressed, and the generation of wrinkles can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view of a copper-clad laminate according to one embodiment of the present invention.

[0020] The description of the accompanying symbols is as follows:

[0021] 1: Copper clad laminate;

[0022] 10: basement membrane;

[0023] 20: conductor layer;

[0024] 21: base metal layer;

[0025] 22: Copper layer. DETAILED DESCRIPTION

[0026] Hereinafter, embodiments of the present invention will be described based on the drawings.

[0027] like Figure 1 As shown, a copper-clad laminate 1 according to an embodiment of the present invention is composed of a base film 10 and a conductor layer 20 formed on the surface of the base film 10. The conductor layer 20 is composed of a base metal layer 21 and a copper layer 22. The base metal layer 21 and the copper layer 22 are sequentially laminated on the surface of the base film 10. Figure 1 As shown, the conductor layer 20 may be formed on only one side of the base film 10 , or the conductor layer 20 may be formed on both sides of the base film 10 .

[0028] The base film 10 is made of a thermoplastic resin. The thermoplastic resin preferably has properties of low dielectric constant and low dielectric loss. In this case, the flexible printed circuit board manufactured using the copper clad laminate 1 is suitable for high frequency use.

[0029] Thermoplastic resins are not particularly limited, and examples thereof include liquid crystal polymer (LCP), polyetheretherketone (PEEK), polyethylene naphthalate (PEN), fluororesins (PTFE, PFA, FEP, ETFE, PCTFE), thermoplastic polyimide (PI), and cycloolefin polymer (COP). Therefore, as the base film 10, a film composed of the aforementioned thermoplastic resin can be used as a whole. In addition, as the base film 10, a film having a core material composed of a thermosetting resin such as a thermosetting polyimide and a surface layer composed of the aforementioned thermoplastic resin can also be used.

[0030] The thermoplastic resin may contain other components within the range that does not damage the physical properties of the base film 10 and the copper-clad laminate 1. For example, polymers such as polyethersulfone, polyetherimide, polyamide, polycarbonate, and polyphenylene ether, and additives such as antioxidants and antistatic agents may also be contained in the thermoplastic resin. In addition, for the purpose of improving the handling properties as a film, inorganic materials such as silica and clay, and fillers such as fibers may be blended into the thermoplastic resin.

[0031] The thickness of the base film 10 is not particularly limited, but is preferably 10 μm or more. When the thickness of the base film 10 is 10 μm or more, wrinkles are less likely to occur in the base metal layer 21 during film formation.

[0032] The base film 10 is preferably subjected to a dehydration treatment. The dehydration treatment removes water contained in the resin. This can prevent the decrease in adhesion between the base film 10 and the base metal layer 21 due to water contained in the resin.

[0033] The surface of the base film 10 in contact with the base metal layer 21 is preferably subjected to surface modification. The surface modification is performed by, for example, plasma treatment, ion beam irradiation, or ultraviolet irradiation. After the surface modification, the resin surface becomes clean and the fragile layer is removed. In addition, by introducing polar groups into the resin surface, the adhesion of the interface with the base metal layer 21 can be improved.

[0034] The base metal layer 21 is formed on the surface of the base film 10 by dry plating. The dry plating method is not particularly limited, and examples thereof include vacuum evaporation, sputtering, and ion plating. Among these, sputtering is preferred.

[0035] For example, a roll-to-roll sputtering device can be used to form a base metal layer 21 on the surface of the base film 10. More specifically, a long strip of base film 10 is installed between a reel and a reel in the sputtering device. After the sputtering device is evacuated, argon gas is introduced and maintained at about 0.13 to 1.3 Pa. In this state, while the base film 10 is transported at a speed of about 1 to 20 m / min, power is supplied to the cathode and sputtering discharge is performed, so that the base metal layer 21 is continuously formed on the surface of the base film 10.

[0036] The base metal layer 21 is formed of an alloy containing at least two elements selected from the group consisting of nickel, chromium, vanadium, titanium, molybdenum and copper. Inevitable impurities of 1% by weight or less contained in the sputtering target may be present in the base metal layer 21. Generally, the composition of the sputtering target and the metal thin film to be formed is almost the same. If a sputtering target having a desired composition is used as the base metal layer 21, a base metal layer 21 having the same composition can be formed.

[0037] The average film thickness of the base metal layer 21 is preferably 0.3 to 1.9 nm. When the base metal layer 21 is formed by sputtering, the average film thickness of the base metal layer 21 can be adjusted by the conveying speed of the base film 10 and the sputtering conditions.

[0038] If the average film thickness of the base metal layer 21 is set to be 0.3 nm or more, the adhesion between the base film 10 and the conductor layer 20 can be maintained. On the other hand, if the average film thickness of the base metal layer 21 is less than 0.3 nm, the etching solution will penetrate during circuit processing, and the circuit part will float, so the circuit peeling strength will decrease.

[0039] In addition, if the average film thickness of the base metal layer 21 is set to 1.9 nm or less, the temperature rise of the base metal layer 21 during film formation can be suppressed. Therefore, even if the base film 10 is made of a thermoplastic resin that does not have the heat resistance of a thermosetting resin, the generation of wrinkles can be suppressed.

[0040] The thinner the base metal layer 21 is, the more preferable it is to suppress the generation of wrinkles in the base film 10. Therefore, the average film thickness of the base metal layer 21 is more preferably 1.5 nm or less, further preferably 1.0 nm or less, and particularly preferably 0.5 nm or less.

[0041] In addition, if the pulse flowing in the line becomes a high-frequency region, a large amount of current will flow on the surface of the line due to the skin effect. Compared with the copper layer 22, the conductivity of the base metal layer 21 is lower, so the thicker the base metal layer 21, the greater the transmission loss. Conversely, the thinner the base metal layer 21, the lower the transmission loss. If the average film thickness of the base metal layer 21 is 1.9nm or less, it is considered that the transmission loss can be sufficiently reduced.

[0042] The copper layer 22 is formed on the surface of the base metal layer 21. Although not particularly limited, the thickness of the copper layer 22 is generally 10 nm to 18 μm. The copper layer 22 can be formed by dry plating, wet plating, or a combination of dry plating and wet plating.

[0043] When forming a thin copper layer 22 having a thickness of 50 nm or less, the copper layer 22 can be formed by dry plating alone. Examples of dry plating methods include vacuum evaporation, sputtering, and ion plating. For example, if a target for the base metal layer 21 and a copper target are provided in a sputtering device, the base metal layer 21 and the copper layer 22 can be formed continuously.

[0044] When forming a thick copper layer 22, a copper thin film layer may be formed by dry plating and then a copper-plated film may be laminated by wet plating. Thus, a copper layer 22 having a desired thickness can be formed economically. When forming a copper-plated film by wet plating, only electroplating may be performed, or a primary plating may be performed by electroless plating and then a secondary plating may be performed by electroplating.

[0045] Example

[0046] Next, embodiments are described.

[0047] (Common conditions)

[0048] Dehydration

[0049] The long base film is placed in a vacuum device having a roll-to-roll mechanism, and the base film is heated and dehydrated by an infrared heater while being conveyed while the pressure in the device is kept at 1 Pa or less by a vacuum pump.

[0050] Surface modification

[0051] The pressure in the vacuum device is set to 1×10 -4 After the pressure reaches 2.5 Pa or less, oxygen gas is introduced to make the pressure 2.5 Pa. In this state, the surface of the base film is irradiated with direct current discharge plasma for several seconds.

[0052] Sputtering

[0053] The pressure in the sputtering device was set to 1×10 -4 After the pressure was reduced to 0.3 Pa or less, argon gas was introduced to make the pressure 0.3 Pa. In this state, a base metal layer and a copper thin film layer were formed on one side of the base film. Here, the thickness of the copper thin film layer was 100 nm.

[0054] ·plating

[0055] Copper sulfate solution was used as the plating solution and 2A / dm 2 Electroplating was performed at a current density of 1000 Å to form a copper plating film with a thickness of 12 μm on the surface of the copper thin film layer. Thus, a copper clad laminate was obtained.

[0056] Characteristic evaluation

[0057] As a measure of the initial adhesion between the base film and the conductor layer, the peel strength was measured by the method according to IPC-TM-650, NUMBER 2.4.9. Here, after the dry film was laminated on a part of the copper-clad laminate to form a photosensitive resist film, it was exposed and developed, and the conductor layer was removed by etching with a ferric chloride solution. Thereafter, the resist was removed to form a 1 mm wide lead for peel strength evaluation. Moreover, the peeling angle was 90°.

[0058] (Example 1)

[0059] A liquid crystal polymer film with a thickness of 50 μm (Vecstar CTZ manufactured by Kuraray Co., Ltd., the same below) was used as the base film. The base metal layer was formed by sputtering using a 20 mass% Cr-Ni alloy target. Here, the average film thickness of the base metal layer was 0.3 nm. The peel strength of the obtained copper-clad laminate was 344 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0060] (Example 2)

[0061] A polyetheretherketone film (EXPEEK manufactured by Kurabo Co., Ltd.) with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was set to 0.3 nm. The peel strength of the obtained copper-clad laminate was 328 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0062] (Example 3)

[0063] A polyethylene naphthalate film (Teonex Q83 manufactured by Teijin Thin Film Solutions Co., Ltd.) with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was set to 0.3 nm. The peel strength of the obtained copper-clad laminate was 323 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0064] (Example 4)

[0065] A fluororesin film (manufactured by AGC Co., Ltd., Fluon+EA-2000) with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass% Cr-Ni alloy target. Here, the average film thickness of the base metal layer was 0.3 nm. The peel strength of the obtained copper-clad laminate was 309 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0066] (Example 5)

[0067] A thermoplastic polyimide film (Pixio SR, manufactured by Kaneka Co., Ltd.) with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was 0.3 nm. The peel strength of the obtained copper-clad laminate was 349 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0068] (Example 6)

[0069] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 7 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was 0.5 nm. The peel strength of the obtained copper clad laminate was 356 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0070] (Example 7)

[0071] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 35 mass % Cu-Ni alloy target. Here, the average film thickness of the base metal layer was 1.5 nm. The peel strength of the obtained copper-clad laminate was 382 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0072] (Example 8)

[0073] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 7 mass % V-Ni alloy target. Here, the average film thickness of the base metal layer was 0.8 nm. The peel strength of the obtained copper clad laminate was 365 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0074] (Example 9)

[0075] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 28 mass % Mo-Ni alloy target. Here, the average film thickness of the base metal layer was set to 1.0 nm. The peel strength of the obtained copper-clad laminate was 391 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0076] (Example 10)

[0077] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 7.5 mass % Ti-Ni alloy target. Here, the average film thickness of the base metal layer was 0.9 nm. The peel strength of the obtained copper-clad laminate was 370 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0078] (Example 11)

[0079] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 10 mass % Ni-Cu alloy target. Here, the average film thickness of the base metal layer was 1.9 nm. The peel strength of the obtained copper-clad laminate was 317 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0080] (Comparative Example 1)

[0081] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was 0.2 nm. The peel strength of the obtained copper-clad laminate was 291 N / m. In addition, no wrinkles were observed in the base film after sputtering.

[0082] (Comparative Example 2)

[0083] A liquid crystal polymer film with a thickness of 50 μm was used as the base film. The base metal layer was formed by sputtering using a 20 mass % Cr-Ni alloy target. Here, the average film thickness of the base metal layer was set to 2.0 nm. The peel strength of the obtained copper-clad laminate was 400 N / m. In addition, wrinkles were observed in the base film after sputtering.

[0084] The above Examples 1 to 11 and Comparative Examples 1 and 2 are summarized in Table 1.

[0085] Table 1

[0086]

[0087] For Examples 1 to 11 in which the average thickness of the base metal layer is 0.3 nm or more, the peel strength is 300 N / m or more, and the initial adhesion between the base film and the conductor layer is sufficient. In contrast, for the comparative example in which the average thickness of the base metal layer is 0.2 nm, the peel strength is weaker at 291 N / m. Thus, it can be confirmed that if the average thickness of the base metal layer is 0.3 nm or more, the initial adhesion between the base film and the conductor layer can be maintained.

[0088] In Comparative Example 2 in which the average thickness of the base metal layer was 2.0 nm, wrinkles were observed in the base film after sputtering. This confirmed that the average thickness of the base metal layer should be 1.9 nm or less in order to suppress the occurrence of wrinkles.

Claims

1. A copper-clad laminate, characterized in that: The invention comprises: a base film composed of a thermoplastic resin; A base metal layer formed on the surface of the base film by dry plating; and A copper layer is formed on the surface of the base metal layer, The average film thickness of the base metal layer is 0.3 to 0.9 nm.

2. The copper-clad laminate according to claim 1, wherein: The base metal layer is composed of an alloy containing at least two elements selected from the group consisting of nickel, chromium, vanadium, titanium, molybdenum and copper.

3. The copper-clad laminate according to claim 1, wherein: The entirety or the surface layer of the base film is a film composed of liquid crystal polymer, polyetheretherketone, polyethylene naphthalate, fluororesin, thermoplastic polyimide or cycloolefin polymer.

4. A method for manufacturing a copper-clad laminate, It is characterized in that The method comprises: forming a base metal layer on the surface of a base film composed of a thermoplastic resin by dry plating; a step of forming a copper layer on the surface of the base metal layer, The average film thickness of the base metal layer is 0.3 to 0.9 nm.

5. The method for manufacturing a copper-clad laminate according to claim 4, wherein: The base metal layer is composed of an alloy containing at least two elements selected from the group consisting of nickel, chromium, vanadium, titanium, molybdenum and copper.

6. The method for manufacturing a copper-clad laminate according to claim 4, wherein: The entirety or the surface layer of the base film is a film composed of liquid crystal polymer, polyetheretherketone, polyethylene naphthalate, fluororesin, thermoplastic polyimide or cycloolefin polymer.

Citation Information

Patent Citations

  • Plated laminate and method for manufacturing the same

    JP2014233891A

  • Surface treatment of polyimide film and polyimide film having a thin metal layer

    TW537967B